An experimental approach that assesses in-situ micro-scale damage mechanisms and fracture toughness in thermoplastic laminates under out-of-plane loading. (1st January 2019) - Wafai, H.; Yudhanto, A.; Lubineau, G.; Yaldiz, R.; Verghese, N.
Abstract: Studying the response of laminated composites under out-of-plane loading routinely involves mechanical tests, such as quasi-static indentation or impact. The phenomenology during these tests is so complex that it is difficult to identify different material properties related to each failure mechanism (damage mode). We aim at providing an experimental approach, which is practical and fast, for assessing the in-situ micro-scale damage mechanism and extracting the fracture toughness in thermoplastic laminates under out-of-plane loading. To this end, we developed a dedicated, micro-scale, three-point bending (micro-3PB) test fitted inside a scanning electron microscope (SEM). In a single experiment, we were able: (i) to assess the initiation of a transverse crack, the transverse crack-to-delamination transition, delamination growth, development of shear-induced microcracks during delamination, and fibrillation, and (ii) to evaluate the effective fracture toughness during transverse cracking and delamination under a representative out-of-plane loading. We used this approach to rank two types of glass fiber-reinforced polypropylene cross-ply laminates, i.e., based on either homopolymer PP (ductile matrix) and copolymer PP (less-ductile matrix), according to their relative fracture parameters. We also performed short edge notch bending (SENB), double cantilever beam (DCB) and end-notch flexure (ENF) to obtain the standard fracture toughness values. We found that the relative fracture toughness values obtained by SENB, DCB and ENF are comparable with that of micro-3PB results. Furthermore, ENF results showed that the delamination process during micro-3PB is dominated by Mode-II fracture.